Answer:
2x (x-1)
Explanation:
We have to find the least common denominator of the fraction
![(4)/(x)+(2x)/((x-1))+ (x+3)/(2x)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/w9xo2pduhlv75s97549qz5y976bwmtc7vy.png)
Least common denominator is the expression which should be divisible by all the denominators.
so, factors of x = 1. (x)
factors of (x-1) = 1. ( x-1 )
factors of 2x = 2. (x)
Therefore, expression which will be divisible by all denominators will be
= 2(x) (x-1)
= 2x (x-1)
2x (x-1) will be the least common denominator.